Analisis Audit Managment Analisis Audit Manajemen Pengelolaan Fungsi SDM Untuk Meningkatkan Kinerja Karyawan Di Klinik SM Kabupaten Bandung: Analisis Audit Manajemen - Sihombing, Kristin (Institut Kesehatan Immanuel, 2023)
Human resources are an important element in achieving organizational goals. In general, leaders expect good performance in completing their tasks. Therefore, to determine employee performance, organizations carry out an assessment of the overall function and role of HR. Decreased performance seen in achieving organizational profits, high employee turnover, and high levels of customer complaints are indications of the need for improvement. These improvements can be carried out through management audits, where the audit stage is carried out by identifying weaknesses and providing recommendations for improvements to existing deficiencies. The research method used in this research is descriptive-qualitative. Data collection techniques include interviews, observation, and documentation studies. The stages in conducting a management audit are: preliminary audit, review of management system control, follow-up audit, and reporting and follow-up with the scope of audited management, starting with recruitment, human resource management, and termination of employment. There are three main elements in this audit target, namely criteria, causes, and effects. From this research, the results obtained show that the management of HR functions starts with planning, recruitment, selection, orientation and placement, training and development, performance appraisal, career planning and development, reward and remuneration systems, occupational safety and health, and employee satisfaction. and termination of employment relations, which have been implemented partially, but there are still several obstacles that result in the management of human resource functions not being implemented optimally. Based on the findings obtained through this audit, it is hoped that there will be improvements in the management of human resources functions.